Design of Solar of Cell and PLN Using Automatic Transfer Switch (ATS) for Minimarket Loads in Sorek Satu Area - Kurniawan Trisna Rinaldi; Rajagukguk, Antonius (International Journal of Electrical, Energy and Power System Engineering, 2022)
Solar energy is an unlimited amount of renewable energy and can be used as a power plant that can be used to meet the electrical energy needs of an area, especially areas affected by the equator. Utilization of solar energy still cannot be applied optimally in some areas. In this study, the use of solar energy is used as the main source of electricity to be used by a minimarket. The use of this solar energy generator is equipped with a backup generator, namely the PLN generator, the selection is intended so that the utilization of solar energy can be maximized. The use of these two power plants in a hybrid manner requires a device so that the transfer from one generator to another can be done automatically. In this study, the tool used is the automatic transfer switch (ATS). The work parameters carried out by ATS are based on reading the battery voltage value. If the battery voltage is 10.8V – 13.2V, the solar energy generator will work to supply the minimarket load, and if the battery voltage does not reach 10.8V, the PLN generator will work to supply the minimarket load.